2009
DOI: 10.1039/b900590k
|View full text |Cite
|
Sign up to set email alerts
|

Polymer functionalization and solubilization of carbon nanosheets

Abstract: Few-layer graphene materials or "carbon nanosheets" were covalently functionalized with poly(vinyl alcohol) via ester linkages, and the resulting functionalized sample became soluble, allowing solution-phase processing for various purposes such as the fabrication of polymer-carbon nanosheets composites containing no dispersion agents or any other foreign substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(116 citation statements)
references
References 27 publications
2
112
0
1
Order By: Relevance
“…Previous research reported that the inter-layers of graphite can be intercalated by various molecular or ions. 19,20 In addition, the XPS data of GP shows that oxygen functional groups are introduced into the surface of graphite (Table 1). Therefore, the increased interlayer spacing is due to the formation of oxygen groups on the surface of graphene and exfoliation of graphite nanoplatelets with a thickness innanometer scale for complete oxidation efficiency by avoid graphite core/graphite oxide shell particles.…”
Section: -14mentioning
confidence: 99%
“…Previous research reported that the inter-layers of graphite can be intercalated by various molecular or ions. 19,20 In addition, the XPS data of GP shows that oxygen functional groups are introduced into the surface of graphite (Table 1). Therefore, the increased interlayer spacing is due to the formation of oxygen groups on the surface of graphene and exfoliation of graphite nanoplatelets with a thickness innanometer scale for complete oxidation efficiency by avoid graphite core/graphite oxide shell particles.…”
Section: -14mentioning
confidence: 99%
“…Functionalized GO derivatives can fulfill specific requirements for various applications. Amine-functionalized porphyrin Pyrrolidine fullerene [74] N-Containing heterocyclic compounds [75] Hydroxyl Polyoxyethylene sorbitol anhydride monolaurate [76] π-π stacking Polyaniline [77] The epoxy groups of GO can be easily attacked by nucleophilic regents, resulting in a nucleophilic substitution reaction to open the epoxy rings. The typically used nucleophilic reagents are organic amine compounds bearing a lone pair of electrons.…”
Section: Functionalized Derivatives Of Gomentioning
confidence: 99%
“…This type of modification has a special interest in the dispersion of functionalized GO in different solvents (polar or non-polar), this is due to the fact that the family of silanes provide a wide range of terminal functional groups. The functionalization of GO via carboxylic acids is one of the most common approaches and is possible by prior activation of these groups through various agents such as thionyl chloride (SOCl 2 ) (Niyogi, Bekyarova et al 2006;Liu, Xu et al 2009;Zhang, Huang et al 2009;Karousis, Economopoulos et al 2010;Zhuang, Chen et al 2010), 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) (Liu, Robinson et al 2008), N, N'-dicyclohexylcarbodiimide (DCC) (Veca, Lu et al 2009) and 2-(7-aza-1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (Hatu) (Mohanty and Berry 2008). Subsequent addition of nucleophilic species, such as amines and hydroxyl, allow the formation of covalent bonds with functional groups of the graphene oxide through formation of amide or ester groups.…”
Section: Covalent Functionalizationmentioning
confidence: 99%